Trichoscopic Signs in Dermatomyositis, Systemic Lupus Erythematosus, and Systemic Sclerosis: A Comparative Study of 150 Patients - Chanprapaph K. (2023)
Background: Hair and scalp involvement is prevalent in connective tissue diseases (CTDs). Trichoscopic features may provide a diagnostic implementation and enable differentiation among CTDs; however, a direct comparison of these signs among CTD patients is lacking. Objectives: To compare trichoscopic findings in dermatomyositis (DM), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc) as well as determine their distinctive features and associations with disease activity. Methods: Trichoscopic photographs were taken from DM, SLE, and SSc patients and further evaluated for hair shaft and scalp surface abnormalities. Data regarding patients' clinical manifestations, laboratory results, and disease activity were analyzed. Results: One hundred fifty participants, consisting of 30 DM, 60 SLE, and 60 SSc patients, were included. Perifollicular red-brown pigmentation, brown scattered pigmentation, and white patches were exclusive findings in DM, SLE, and SSc, respectively (p < 0.001). A multinomial logistic regression analysis revealed that DM demonstrated higher odds for having microaneurysmal blood vessels than SLE and SSc (odds ratio [OR] = 22.22, 95% confidence interval [CI] = 1.73-285.13, p = 0.017, and OR = 15.34, 95% CI = 1.36-177.59, p = 0.029, respectively). Polymorphic vessels forming a telangiectatic network suggested SSc over SLE (OR = 12.83, 95% CI = 1.35-121.98, p = 0.026), while avascular areas were more pronounced in SSc than DM and SLE (OR = 43.24, 95% CI = 5.17-361.67, p = 0.001, and OR = 0.03, 95% CI = 0.01-0.24, p = 0.001, respectively). In a quantile regression analysis, perifollicular red-brown pigmentation, reduction in hair diameter, and the absence of thin arborizing vessels were linked to higher disease activity in DM, SLE, and SSc, respectively (all p < 0.05). Conclusions: Trichoscopy is a valuable tool possessing diagnostic and prognostic values for CTDs. Specific trichoscopic features allow adequate distinction between DM, SLE, and SSc and may help identify active disease.